Magnetic resonance imaging for non-invasive clinical evaluation of normal and regenerated cartilage. Issue 5 (17th August 2021) - Xu, Xian; Gao, Jingming; Liu, Shuyun; Chen, Liang; Chen, Min; Yu, Xiaoye; Ma, Ning; Zhang, Jun; Chen, Xiaobin; Zhong, Lisen; Yu, Lin; Xu, Liming; et al.
Abstract: With the development of tissue engineering and regenerative medicine, it is much desired to establish bioimaging techniques to monitor the real-time regeneration efficacy in vivo in a non-invasive way. Herein, we tried magnetic resonance imaging (MRI) to evaluate knee cartilage regeneration after implanting a biomaterial scaffold seeded with chondrocytes, namely, matrix-induced autologous chondrocyte implantation (MACI). After summary of the T2 mapping and the T1-related delayed gadolinium-enhanced MRI imaging of cartilage (dGEMRIC) in vitro and in vivo in the literature, these two MRI techniques were tried clinically. In this study, 18 patients were followed up for 1 year. It was found that there was a significant difference between the regeneration site and the neighboring normal site (control), and the difference gradually diminished with regeneration time up to 1 year according to both the quantitative T1 and T2 MRI methods. We further established the correlation between the quantitative evaluation of MRI and the clinical Lysholm scores for the first time. Hence, the MRI technique was confirmed to be a feasible semi-quantitative yet non-invasive way to evaluate the in vivo regeneration of knee articular cartilage.